Solution Selection in Digital Construction Design – A Lazy User Theory Perspective. (2015) - Merschbrock, Christoph; Tollnes, Tor; Nordahl-Rolfsen, Christian
Abstract: The construction industry is in the midst of a transition with traditional design systems being gradually replaced by novel virtual modeling technologies. This transition takes place gradually rather than radically and while new systems (e.g. Building Information Modelling) become increasingly diffused in the industry, many legacy systems and practices are left intact. This leads to situations where designers have several different information systems at their disposal to fulfill their information needs. This is amplified by software vendors releasing a myriad of new design systems. How individual designers select an information system from several available options to fulfill their information need is discussed in this article. The findings suggest that construction designers will most often select a design system solution fulfilling their information needs with the least effort on their part. The theoretical approach supporting the analysis in this article is the so-called Lazy User Theory (LUT). LUT explains how users select among available solutions when there are numerous products and services possible. Preferred solutions reflect (1) a user's perceived information need (e.g. function of urgency, type, and depth) and (2) the user-state which is the situation in which the user is at the moment of information need. The findings presented in this article are derived from a case study conducted in a Norwegian construction project. The findings show that users' choice of design systems reflected local and circumstantial considerations rather than what is best for the project. This article is important for several reasons. First it contributes to an understanding of what are influential considerations for designers when selecting design solutions. Second, it illustrates how local system selection decisions may affect the digital work at project level.